Proportion of depression and its determinants among type 2 diabetes mellitus patients in various tertiary care hospitals in Mangalore city of South India - Nitin Joseph (Indian Journal of Endocrinology and Metabolism, 2013)
Background: Depression is found to be common among patients with diabetes and it is associated with poor outcomes in disease control. This study was carried out to find out the proportion and determinants associated with depression among patients with established type 2 diabetes mellitus (T2DM) in various tertiary care hospitals in Mangalore city of south India. Materials and Methods: This study was conducted in one government and three private tertiary care hospitals in Mangalore in December 2010. All consenting patients with confirmed diagnosis of T2DM were interviewed and screened for depression by administering the 9-item PRIME-MD Patient Health Questionnaire (PHQ-9). Results: Of the 230 T2DM patients, 119 (51.7%) were males. The mean age of all participants was 53.61 ± 10.7 years. The median duration of T2DM was found to be 12.1 ± 7.35 years. Among the participants, 71 (30.9%) met the criteria for moderate depression, 33 (14.3%) for severe depression, and the remaining 126 (54.8%) had no clinically significant depression. Only 26 (11.3%) patients were already aware that they were depressed, of whom just 3 had taken medical consultation. Among the risk factors, depression was found to be significantly associated with older age, female gender, low socioeconomic status, unskilled and retired employment status, having complications due to T2DM or comorbidities like hypertension and coronary artery disease, being overweight and being on insulin syringe injections. Conclusion: This study found a high proportion of depression among patients with T2DM. Therefore the care of individuals with diabetes mellitus (DM) should include the screening and possible treatment of depression in order to achieve and sustain treatment goals.